5
$\begingroup$

I solved this interesting integral online: $$I = \int\limits_{-1}^{1} \arctan(e^x)dx $$ Now I tried the substitution $u=e^x$ but it lead me nowhere. I was looking at the following post which was solved in a beautiful way Integrate $\int_0^{\pi/2} \frac{1}{1+\tan^\alpha{x}}\,\mathrm{d}x$. From there I found this very interesting article http://www.maa.org/sites/default/files/pdf/mathdl/CMJ/Nelsen39-41.pdf which has the integral I posted at the end as a question to the reader.

Looking at the graph of $\arctan(e^x)dx$ on the interval $-1 \leq x \leq 1$ I conjectured that $I=\frac{\pi}{2}$. I used the following method to prove it: \begin{eqnarray} -e^{-x}&=&\frac{-1}{e^x}\\&=& \frac{-1}{\tan\{ \arctan(e^x) \} }\\&=&-\cot\{ \arctan(e^x) \}\\ &=& \tan \left\{\arctan(e^x)-\frac{\pi}{2} \right\}\\ \end{eqnarray} For the last equality I used the fact that $\cot(\theta) =-\tan\left(\theta -\frac{\pi}{2}\right) $. Now we take the arctan of both sides to obtain: $$\arctan(-e^{-x}) = \arctan(e^x)-\frac{\pi}{2}$$

Finally I use the fact that $\arctan(-\theta)=-\arctan(\theta)$ and add $\frac{\pi}{4}$ to both sides of the last equation to obtain: $$-\arctan(e^{-x}) +\frac{\pi}{4}= \arctan(e^x)-\frac{\pi}{4} $$ So it is established that the function $f(x) = \arctan(e^x)-\frac{\pi}{4}$ is an odd function. Thus $$I_2 = \int\limits_{-1}^{1} \left[ \arctan(e^x)-\frac{\pi}{4} \right]dx = 0 $$ Now $$I = \int\limits_{-1}^{1} \arctan(e^x)dx = I_2 + \int\limits_{-1}^{1} \frac{\pi}{4}dx =\frac{\pi}{2} $$ I thought this integral was really interesting and I was wondering if anyone else has any different ways of solving it, possibly with a clever substitution. I was especially amazed at how easily it could be solved because integrals with arctan usually give me a lot of trouble.

Also, I think we can extend this to a broader result where we replace $x$ by any arbitrary odd function $g(x)$ and show that $$I = \int\limits_{-a}^{a} \arctan(e^{g(x)})dx = \frac{a \pi}{2}$$ for any odd function $f(x): (-a,a) \to\Bbb R$. Essentially the proof for this would follow the exact same reason as above right?

So if anyone has another method of computing the original integral I am definitely interested in reading your solutions! Thanks in advance for any input and ideas! Also thanks to Ron Gordon for his nice answer on the question I linked, the answer given there inspired me to look for different ways of trying to solve this integral that I normally would have given up on.

$\endgroup$
1
2
$\begingroup$

$g(x)$ need to be an odd function, otherwise $f(x)=\arctan(e^{g(x)})-\pi/4$ is not an odd function.

One simple test is at least $f(x=0)$ should be $0$, which is not satisfied by your choice of $g(x)=1$.

$\endgroup$
2
  • $\begingroup$ Yes you are right! Thanks, I see that it is necessary now. I am still interested in anyone having another derivation for the original integral $I$ though! $\endgroup$ – Slugger Dec 16 '13 at 3:08
  • $\begingroup$ As far as I know, without that "odd function" technique, there is no simple ways to calculate this. The [indefinite integral][1] is really messy. [1]: wolframalpha.com/input/?i=integrate%5Barctan%5Be%5Ex%5D%2Cx%5D $\endgroup$ – MoonKnight Dec 16 '13 at 3:29
0
$\begingroup$

was working on something similar

integration by parts, noticing the initial integral is related to a form of the integral of sech

$I = \int\limits_{-1}^{1} \arctan(e^x)dx$

$= [x \arctan(e^x)] - \int\limits_{-1}^{1} x e^x / (1 + e^{2x})dx$

$= [x \arctan(e^x)] - \int\limits_{-1}^{1} x / (e^{-x} + e^{x})dx$

$= [x \arctan(e^x)] - (1/2)\int\limits_{-1}^{1} x sech(x)dx$

is then odd i think and equals $[x \arctan(e^x)]$

I got Nelsen's answer of pi/2, not sure why the x arctan part works out as that yet, but numerically it did

$\endgroup$
1
  • $\begingroup$ actually you proved that last part, it was what I was looking for in the first place thanks! $\endgroup$ – Cato Mar 20 '17 at 18:16
0
$\begingroup$

I have found another way to integrate this integral,first you have to know this identity, very useful for integrals with arctan $$\arctan(y)+arctan(1/y) =\frac{\pi}{2}\qquad (1)$$ with x positive or equal to 0, and $$\arctan(y)+arctan(1/y) =\frac{-\pi}{2}$$ for y negative. The first step is separate the integral

$$\int\limits_{-1}^{1} \arctan(e^x)dx=\int\limits_{0}^{1} \arctan(e^x)dx+\int\limits_{-1}^{0} \arctan(e^x)dx\qquad (2)$$ after that in the seconnd integral use this substitution (x=-y) and we get

$$\int\limits_{-1}^{0} \arctan(e^x)dx=\int\limits_{0}^{1} \arctan(e^-y)$$ then wecan use this and put it in (1) (and replace x=y because is the same what variable we use) and we get $$\int\limits_{0}^{1} \arctan(e^x)dx+\int\limits_{0}^{1} \arctan(e^-x)dx$$ after we use (2) and we get $$\int\limits_{0}^{1} \frac{\pi}{2}dx$$=\frac{\pi}{2} Then i tryed to generalize and I resolved the same first integral with x=x^3, if you want you can try to prove it. Finally we can generalize for g(x) if this function is odd

$$\int\limits_{-1}^{1} \arctan(e^{g(x)})dx=\int\limits_{0}^{1} \arctan(e^{g(x)})dx+\int\limits_{-1}^{0} \arctan(e^{g(x)})dx$$ we subtitue (x=-y) in the second integral and omitting steps we get $$\int\limits_{-1}^{1} \arctan(e^{g(x)})dx=\int\limits_{0}^{1} \arctan(e^{g(x)}-e^{g(-x)})dx=\int\limits_{0}^{1} \frac{\pi}{2}dx=\frac{\pi}{2}$$

for a and -a in the limits we can use the same method, if you can´t do it i will explain it,thank you for reading and goodbye.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.